Application of first break tomography technology in shallow loess layer detection - Wang, Chi (International Journal of Natural Resources and Environmental Studies, 2026)
The near-surface structure and unique physical properties of loess-covered areas render traditional geophysical methods ineffective in achieving high-precision structural detection of loess layers, thereby restricting regional resource exploration, geological hazard prevention, and optimal utilization of water resources. Focusing on the loess layers in the Qianyang area, this study aims to address the challenge of fine characterization of loess layer structures using first-break tomographic imaging technology. Firstly, the key parameters such as vertical stratification and velocity of loess layer are obtained through the investigation and analysis of geological data, and the initial geological geophysical model is constructed; Then, typical models such as horizontal surface, undulating surface and fault are designed to carry out forward simulation, analyze the influence of terrain and fault on first break propagation, and verify the applicability of first break tomography technology; Finally, the tomographic inversion of the actual data in the study area is carried out, and the comprehensive interpretation is completed by combining the seismic reflection profile. The results indicate that topographic relief causes regional shifts in first-break travel times, while faults induce first-break signal anomalies. However, first-break tomographic imaging technology can effectively mitigate these effects, enabling accurate identification of key geological interfaces such as the internal structures of individual loess layers, loess-bedrock interfaces, and concealed faults, among others. This study confirms the effectiveness of first-break tomographic imaging technology for delineating loess layer structures.